Formulation of Pecel Chili Sauce with the Proportion of Peanuts and Cashew Nuts, and the Use of Black Garlic - Rohmah, Nova Ainur; Yulistiani, Ratna; Wicaksono, Luqman Agung (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
Pecel chili sauce is a food made from peanuts combined with several spices that are ground and mixed into a paste, then served as a complementing sauce for vegetable pecel. The ingredients used affect the chemical and organoleptic properties of the pecel chili sauce. This study aims to determine the best formulation of pecel chili sauce with the treatment of the proportion of peanuts : cashew nuts and the proportion of garlic:black garlic based on chemical and organoleptic parameters. This study uses a Completely Randomized Design (CRD) with a factorial pattern, two factors, and two repetitions. The first factor is the proportion of peanuts : cashew nuts (100%:0%, 75%:25%, 50%:50%), and the second factor is the proportion of garlic:black garlic (100%:0%, 0%:100%, 50%:50%). The data were analyzed using ANOVA and followed by the DMRT test at the 5% level. The pecel chili sauce with the proportion of peanuts : cashew nuts 75%:25% and garlic:black garlic 0%:100% was the best treatment, resulting in pecel chili sauce with a moisture content of 12.53%, protein content of 10.63%, fat content of 12.83%, and antioxidant activity of 60.97%, as well as organoleptic values of taste 3,68 (liked), smell 3,52 (liked), and color 3,72 (liked). Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 3: Good Health and Well-beingSDG 9: Industry, Innovation, and InfrastructureSDG 12: Responsible Consumption and ProductionSDG 15: Life on Land